Degradation of betaine aldehyde dehydrogenase transgenic maize BZ-136 straw and its effects on soil nutrients and fungal community - Liu, Xuesheng; Zeng, Xing; Zhu, Yuhang; Wang, Wei; Huang, Siqi; Qiao, Xinxin; Wang, Zhenhua; Di, Hong; Qu, Juanjuan (Frontiers in Microbiology, 2023)
The development of salt-alkali tolerant genetically modified crops represents an important approach to increase grain production in saline-alkali soils. However, there is a paucity of research on the impact of such genetically modified crops on soil microbial diversity. This study aims to investigate the straw degradation of betaine aldehyde dehydrogenase (BADH) transgenic maize BZ-136 and its effects on soil chemical properties, fungal community composition, community diversity and ecological function compared to non-transgenic maize Zheng58 straw. The degradation experiments of BZ-136 straw were carried out under a simulated burying condition with saline-alkali soil for 210 days. The results showed that the degradation rate of C and N of BZ-136 straw was significantly faster than that of Zheng58 in the early stage (p < 0.05). Compared to Zheng58, the straw degradation of BZ-136 increased the soil available nitrogen (AN), total phosphorus (TP), and available phosphorus (AP) in the early stage (p < 0.05). The AN content of soil with BZ-136 straw was 18.16 and 12.86% higher than that of soil with Zheng58 at day 60 and 120 (p < 0.05). The TP content of soil with BZ-136 was higher 20.9 and 20.59% than that with Zheng58 at day 30 and 90 (p < 0.05). The AP content of soil with BZ-136 was 53.44% higher than that with Zheng58 at day 60 (p < 0.05). The straw degradation of BZ-136 increased the OTU number of soil fungal community by 127 (p < 0.05) at day 60, and increased Chao1 and Shannon index at day 60 and 180 (p < 0.05). The degradation rate of C and N in BZ-136 straw was higher than that in Zheng58 at early stage, which led to the phased increase of soil AN and TP contents, and the obvious changes of relative abundances (RA) of some genera and guilds. These findings are important as they provide insight into the potential benefits of BADH transgenic crops in upgrading the soil fertility and the fungal community diversity.